Detection of a guanine X adenine base pair in a decadeoxyribonucleotide by proton magnetic resonance spectroscopy. - Kan, L S (1983)
A decadeoxyribonucleotide, d(C-C-A-A-G-A-T-T-G-G) (I), forms a duplex in solution. The base pairing pattern in this duplex was studied by proton nuclear magnetic resonance spectroscopy. Five NH...N hydrogen-bonded proton resonances were observed, and they were assigned by nuclear Overhauser enhancement experiments as well as by comparison to five previously assigned NH...N hydrogen-bonded proton resonances in a self-complementary duplex of similar sequence, d(C-C-A-A-G-C-T-T-G-G) (II). The results suggest that the central -G-A- residues of I form G X A base pairs in the helical state. The fact that the H2 proton of A at the sixth position from the 5' end of I showed nuclear Overhauser enhancement when the NH...N hydrogen-bonded proton resonance of G X A was irradiated suggests that the bases of the G X A base pair are oriented in an anti-anti conformation. Comparison of the linewidths at the half height of the NH...N hydrogen-bonded proton resonances of I at 1 degree C suggest that the G X A base pairs are less stable than adjacent A X T base pairs.